Performance Drivers & Future Growth Prospects of the Logistic Service Providers (3PL) in the Indian Surface Logistics Sector - Garg, Molika (Digital Repository of Theses, 2025)
This research studies the surface logistics business in India and attempts to decipher why 3PL works and how they can grow. Its goal is to forecast the future of the industry in light of the impacts of economic growth, globalization, and market circumstances by analysing the internal and external factors that influence the efficacy of LSPs. Both primary and secondary data are used for the research – online surveys of supply chain managers and transport professionals and secondary data from authentic Indian logistics data sets. It is found that the research results show that operational efficiency and technology implementation improve LSP’s performance, but categorizing critical factors does not affect the outcome. Moreover, human resource management implementation is positively related to LSP’s performance. A favourable correlation between LSPs' expectations for the future and policy shifts, technological advancements, and real-time data analytics was also found in the study. Given these results, it's clear that LSPs need to pay close attention to HRM, technology, and operations if they want to succeed. Findings from the study suggest actions to take in order to take advantage of these growth prospects, such as increasing digital technology use and strengthening supply chain and environmental resilience. Thus, this study's findings provide light on the current state and potential future of India's surface logistics sector, which can help third-party logistics providers become more competitive and sustainable, which in turn can help India's economy grow.